Novel GALC Mutations Cause Adult-Onset Krabbe Disease With Myelopathy in Two Chinese Families: Case Reports and Literature Review - Zhong, Junfei; Jiang, Fei; Yang, Huan; Li, Jing; Cheng, Jian; Zeng, Qiuming; Xu, Qian (Frontiers in Neurology, 2020)
Krabbe disease (KD), also referred to as globoid cell leukodystrophy, is a rare autosomal recessive lysosomal storage disorder caused by β-galactocerebrosidase (GALC) deficiency. Most patients affected by this disease are infants; less than 10% of cases suffer from adult-onset KD. In this study, two Chinese males presented with long-term progressive weakness in their limbs. Magnetic resonance imaging of the brain and spinal cords of these patients revealed lesions with abnormally high signal intensity on T2-weighted and T2W fluid-attenuated inversion recovery images. Whole-exome sequencing was performed for both patients, and four GALC mutations were identified. Case 1 carried a novel deletion mutation (p.T633Tfs*2) and a known missense mutation (p.T529M), while Case 2 carried a novel missense mutation (p.P154H) and a known missense mutation (p.W355C). Previous literature has only rarely reported myelopathy in patients with KD; in this study, we report two cases of adult-onset KD who both experienced myelopathy. We also conducted a literature review of KD and its association with myelopathy. Our findings provide a better understanding of the phenotypic and genotypic profiles associated with adult-onset KD. We recommend that physicians consider KD as a possible diagnosis in cases showing progressive motor dysfunction or gait disorder in association with typical myelopathy.